Basic electrical and electrical engineering - Bhattacharya, S. K.; Devaraj, D. (Pearson India Education Services, 2017)
This comprehensive book on basic electrical engineering covers almost all the topics of basic electrical engineering, ranging from circuits to machines to measurements to power systems. An introduction to basic electronics has also been provided so as to prepare the students for an in-depth study later. The chapters have been developed using the basic principles of learning and motivation. Easy explanation of topics, plenty of examples and illustrations, practice problems and multiple choice questions with answers, and short answer type review questions are the principal features of this book.